To be able to, or to be able not to? That is the question. A problem for the transcendental argument for free will - Elzein, Nadine (Array, 2019)
A type of transcendental argument for libertarian free will maintains that if acting freely requires the availability of alternative possibilities, and determinism holds, then one is not justified in asserting that there is no free will. More precisely: if an agent A is to be justified in asserting a proposition P (e.g. "there is no free will"), then A must also be able to assert not-P. Thus, if A is unable to assert not-P, due to determinism, then A is not justified in asserting P. While such arguments often appeal to principles with wide appeal, such as the principle that ‘ought’ implies ‘can’, they also require a commitment to principles that seem far less compelling, e.g. the principle that ‘ought’ implies ‘able not to’ or the principle that having an obligation entails being responsible. It is argued here that these further principles are dubious, and that it will be difficult to construct a valid transcendental argument without them.